Paying zakat to non-muslims and charity organizations / Nur Athirah Ab Aziz … [et al.] - Ab Aziz, Nur Athirah; Effendey, Nurhusnina Hasny; Mohd Zamri, Zeti Nur Ain; Alias, Siti Nor Najihah; Mohamad Anifah, Siti Nur Athikah (2023)
Zakat is an Islamic faith pillar that demonstrate the development of society and economy. Like the obligation to pray, zakat is clarified in general and not in detail in the Al-Quran. The Qur'an does not explain the rate, nisab, type of property subject to zakat, or zakat conditions, but the Hadith of Rasulullah s.a.w. does. However, the Al-Quran clearly states that zakat must be distributed to eight specific asnaf (Wahid, H., et al. 2010).